STUDI SOCIAL JUDGMENT PERILAKU GEN-Z DI BENGKULU SELAMA MASA PANDEMI - Nurlianti Muzni; Dwi Aji Budiman (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2021)
Generation Z (1997-2012) is a generation that is very close to the growth and development of technology. During the pandemic, information is received by this generation through face-to-face communication in the closest circle, as well as virtual information media that use WhatsApp the most, followed by Instagram, Facebook and Twitter. This study looks at how social judgment involving ego is formed in Generation Z in Bengkulu and their attitudes and behavior during the pandemic. Changing the individual's concept of processing messages that were originally in the form of stimulation, into acceptance, rejection, or noncommitment. Receipt of information is seen when the issue is related or occurs in their immediate environment. Rejection of information when Generation Z ignores health protocols. Meanwhile, the indifferent attitude only runs without knowing the essence of what is being done.